Brillouin light scattering of ion-implanted and annealed diamond surfaces - Motochi, Isaac (My University, 2016)
The sub-surface region of chemical vapour deposition (CVD) diamond was transformed by C+ ion implantation followed by isochronal annealing up to 1200 oC. Different implantation regimes and with different energies at different implantation temperatures would give different thicknesses were studied. This enabled a study in the evolution of the stiffness of the damaged layer as a function of annealing. The technique of choice for this study was the non-destructive Brillouin light scattering (BLS) utilizing two scattering geometries; indirectly scattered phonons (Kr¨uger-type geometry) for temperature anneals up to 600 oC, and the conventional surface ripple mechanism up to 1200 oC. It has been argued that surface acoustic waves (SAW) on a transparent medium are enhanced by applying a thin metallic reflective layer on the surface, this study has showed that opacity of the substrate is key. In fact, bulk modes with SAW-like characteristics emanating from indirect photon scattering off phonons after reflection at the smooth reflective back of the sample dominated down to transmission below 5% which was observed after annealing between 500-600 oC (low annealing temperatures). The other complementing techniques employed to understand the changing structure of the ion implanted diamond were Raman spectroscopy, electromagnetic transmission in the visible range, electron energy loss spectroscopy (EELS) and high-resolution transmission electron microscopy (HRTEM) in addition to theoretical techniques: transport of ions in matter (TRIM), finite element modelling (FEM) and elastodynamic Green’s functions. Although the electronic techniques showed a structurally changing material at the low annealing temperatures, the optical ones did not show significant changes in the ion-damaged material possibly due to lack of distinct interface between the pristine diamond and the ion irradiated region at these lower annealing temperatures.
Keywords: Brillouin scattering.; Electromagnetic waves--Scattering.; Ion implantation.; Diamonds.